Propostas de mudanças sobre os fundos constitucionais de financiamento e a desconfiguraç\~ao progressiva dos instrumentos da política regional brasileira - Guilherme Lopes; Fernando Cezar de Macedo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The present work aims to analyze consolidated changes and still pending change proposals to the Constitutional Financing Funds in the Federal Congress. The issue at stake that we seek to emphasize is the close dispute over funds' resources, as we believe that they are important instruments for the accumulation base and, therefore, draw different interests of federative entities and regional economic groups directly benefited by the appropriation of the economic surplus. Through a bibliographic review and analysis of the current proposals for institutional changes, we observed that substantial changes are underway in the normative, financial and administrative ordinance of the funds. Finally, we concluded that these changes are disconnected from the principles that should guide the fight against regional imbalances, therefore, disconnected from the objectives of the funds and the National Policy for Regional Development (PNDR), which, in theory, should guide their action.
10419/284897
Keywords: P16; R50; R58; 330; Constitutional Financing Fund; regional policies